The Use of Chunking Technique Combined with the Writing Is Thinking Technique to Control Students' Cognitive Load When Learning About the Human Reproductive System - Dwiningtyas Putri, Meirin; Rahmat, Adi; Sanjaya, Yayan (KnE Social Sciences, 2024)
Cognitive load is related to working memory capacity, which affects the cognitive processing system. This study aimed to control the cognitive load of students by using chunking techniques combined with the writing is thinking technique when learning about the human reproductive system. The research was conducted at a senior high school in Tasikmalaya City during the 2020/2021 academic year. 56 research subjects were divided into two groups - the experimental group and the control group. The research method used was quasi-experimental with a post-test-only control group design. Measurement of students’ cognitive load included intrinsic cognitive load (ICL), extraneous cognitive load (ECL), and germane cognitive load (GCL), which was measured using an instrument in the form of a subjective rating scale questionnaire with a scale of 1 – 8. The results showed that learning about the human reproductive system using the chunking technique combined with the writing and thinking technique obtained the average value of a student’s ability to receive and process information was 38.4 (low ICL). The average value of mental effort was 32.8 (low ECL), and the average value of the cognitive load related to student learning outcomes was 73.7 (high GCL). Based on the results of statistical tests with the Mann Whitney two-mean difference test, there were significant differences in the ICL, ECL, and GCL components between the experimental group and the control group, so the use of chunking techniques combined with writing is a thinking technique that can control the cognitive load. The chunking technique combined with writing is a thinking technique that is able to optimize working memory capacity by managing pieces of information and helping students construct knowledge by rewriting the information obtained using their own language. Keywords: chunking techniques, writing is thinking technique, human reproductive system